Scientometric Indicators as a Way to Classify Brands for Customer’s Information - Paun, Mihaela; Tusa, Iris (Journal of Economic Development, Environment and People, 2015)
The paper proposes a novel approach for classification of different brands that commercialize similar products, for customer information. The approach is tested on electronic shopping records found on Amazon.com, by quantifying customer behavior and comparing the results with classifications of the same brands found online through search engines. The indicators proposed for the classification are currently used scientometric measures that can be easily applied to marketing classification.